Negara dan Perlindungan Tenaga Kerja Indonesia (TKI) di Luar Negeri: The State and Protection of Indonesian Migrant Workers (TKI) Abroad - Nur Solikin (Fenomena, 2017)
The precarious situation of Indonesian migrant workers (TKI) often reflects their treatment as second-class citizens, with the state failing to provide adequate legal protection, particularly in destination countries like Malaysia. This article examines the government’s role in protecting its citizens abroad, the specific mechanisms of protection in Malaysia, and how the state assists TKI facing legal and social problems. Using a normative legal approach and analysis of Indonesian Laws No. 37/1999 and No. 39/2004, along with ministerial decrees, the study finds that protection is categorized into preventive, facilitative, and repressive measures. However, implementation remains weak due to over-reliance on private placement companies (PJTKI) and the high number of undocumented workers. The article concludes that the state must take greater diplomatic and legal responsibility, strengthen bilateral cooperation, and improve institutional oversight. Recommendations include creating productive employment domestically, restructuring migrant worker institutions, and enhancing legal aid and surveillance at borders. Situasi rawan yang dialami Tenaga Kerja Indonesia (TKI) di luar negeri kerap mencerminkan perlakuan sebagai warga negara kelas dua, di mana negara gagal memberikan perlindungan hukum yang memadai, terutama di negara tujuan seperti Malaysia. Artikel ini mengkaji peran pemerintah dalam melindungi warganya di luar negeri, mekanisme spesifik perlindungan di Malaysia, serta cara negara membantu TKI menghadapi masalah hukum dan sosial. Dengan pendekatan hukum normatif dan analisis terhadap UU No. 37/1999 serta UU No. 39/2004, ditemukan bahwa perlindungan terbagi menjadi tiga sifat: preventif, fasilitatif, dan represif. Namun, implementasinya masih lemah karena ketergantungan berlebih pada perusahaan jasa TKI (PJTKI) dan tingginya jumlah pekerja ilegal. Artikel ini menyimpulkan bahwa negara harus mengambil tanggung jawab diplomatik dan hukum yang lebih besar, memperkuat kerja sama bilateral, serta meningkatkan pengawasan kelembagaan. Rekomendasi meliputi penciptaan lapangan kerja produktif di dalam negeri, restrukturisasi kelembagaan, serta peningkatan bantuan hukum dan pengawasan di perbatasan.